Strategi Peningkatan Kualitas Sumber Daya Manusia Melalui Program Pembinaan dan Pembiayaan Rumah Tahfidz Al-Qur’an - Fajarwati, Desi; Victorynie, Irnie (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to analyze the planning, implementation, and constraints of the Tahfidz Quran House (RTQ) Financing and Development Program in Musi Rawas Regency, which will be carried out from 2023 to 2024. A qualitative approach was used by collecting data through in-depth interviews with the Secretary of the RTQ Coordination Team, direct observation of several fostered RTQs, and interviews with Tahfidz teachers. The results of the study show that this program aims to improve the quality of human resources through memorization and practice of the Quran, with the target of establishing 200 RTQs evenly in all sub-districts. The implementation of the program includes a strict selection of Tahfidz teachers, adequate learning facilities, and regular incentives for teaching staff. The obstacles faced include the heterogeneity of participants' abilities, communication gaps due to language differences, and uneven distribution of RTQs. However, strategic measures such as a differentiated approach to learning, the use of Indonesian, and results-based management have successfully overcome most of these challenges. This program has a positive impact by creating free Al-Quran education opportunities, increasing community motivation to send children to RTQ, and strengthening religious identity in Musi Rawas Regency. However, capacity building for Tahfidz teachers through training is considered important to face future challenges. Continuous evaluation and support from various parties are needed to maintain the quality and sustainability of the program.